THE NECESSITY OF ENSURING COMPETITIVENESS OF ROMANIAN WINES ON WORLD MARKET - Ion Serban, Dobronauteanu (Economics of Agriculture, 2012)
European wines sector is in a structural crisis for a long time and their stakeholders: producers, EU governments and EU authorities agree that only by increasing the competitiveness, this agro-food product can re-become a success and a positive trend on international markets, according to the quality productions potential. The Community financial support allocations for our countrys wine sector, was stipulated by the Romanians Accession Treaty to the European Union and was implemented by successive regulations for Common Organization of the Wine market R (CE) 1493/1999 and R (CE) 479/08 and included in "Single CMO Regulation" R (CE) 1234/2007 establishing a common organisation of agricultural markets, emphasizing on increasing productivity of Community wine. This paper focuses on updated dynamics in terms of global wine market and measures implementation but also the Romanian producers tendency and efforts to increase the competitiveness.